CRITERIA AND INDICATORS OF THE DEVELOPMENT OF MUSICIAN’S TIMBRE HEARING - Zavadska, Galina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Musical practice constantly lays down requirements to a musician’s hearing. An important tendency of a contemporary musical thinking is the intensification of the timbral beginning, which now starts to come to the foreground as one of the most significant expressive and form-developing means. Timbre hearing is one type of harmonic hearing (Teplov, 1947) and one of the most essential components at teaching a contemporary musician’s hearing, though in the teaching practice it has not been adequately reflected as yet. The development of the ability of hearing to perceive the expressive sense of a timbre sounding is a vital condition for achieving professionalism in a musician’s musical-performing activity. The precondition for a successful development of musical hearing, including that of timbre, is the process of diagnosticating its actual developmental level, which will help a teacher to organize a student’s musically-practical activity.The paper offers criteria and indicators for identifying the developmental level of musician’s timbre hearing.Research Aim: to study the theoretical basis of timbre hearing and to develop criteria and indicators of its development.Research methods: monitoring, modelling.